Urea-Doped ZnO Films as the Electron Transport Layer for High Efficiency Inverted Polymer Solar Cells - Wang, Zongtao; Wang, Zhongqiang; Zhang, Ruqin; Guo, Kunpeng; Wu, Yuezhen; Wang, Hua; Hao, Yuying; Chen, Guo (Frontiers in Chemistry, 2018)
In this paper, urea-doped ZnO (U-ZnO) is investigated as a modified electron transport layer (ETL) in inverted polymer solar cells (PSCs). Using a blend of Poly{4,8-bis[(2-ethylhexyl)oxy] benzo[1,2-b:4,5-b']dithiophene-2,6-diyl-alt-3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophene-4,6-diyl}(PTB7) and [6,6]-phenyl-C71-butyric acid methyl ester (PC71BM) as light absorber, a champion power conversion efficiency (PCE) of 9.15% for U-ZnO ETL based PSCs was obtained, which is 15% higher than that of the pure ZnO ETL based PSCs (7.76%). It was demonstrated that urea helps to passivate defects in ZnO ETL, resulting in enhanced exciton dissociation, suppressed charge recombination and efficient charge extraction efficiency. This work suggests that the utilization of the U-ZnO ETL offer promising potential for achieving highly efficient PSCs. Keywords: polymer solar cells, ETL, ZnO, urea, PCE